Perbandingan kandungan iodium dalam urin antara sampel urin 24 jam dan on spot pada anak usia sekolah - Widya Ayu Kurnia Putri; Dodik Briawan; Hidayat Syarif; Leily Amelia (Jurnal Gizi Klinik Indonesia, 2017)
Background: Urine Iodine Concentration (UIC) is the indicator to assess iodine status. UIC from 24-hour urine collection appropriate to used as a direct measure of the iodine status and helps to validate the estimates intake of iodine. 24-hours urine collection is not practical in large studies and epidemiological surveys because it is quite difficult to complete and accurate collection. WHO/UNICEF/ICCIDD recommend the use of on spot urine collection.Objective: The aim of this study was to compare of 24-hour urine collection and spot urine collection for the assessment UIC in children.Method: The cross-sectional study was applied in Bogor. UIC was measured in 24-hour urine and parallel collected three spot urine namely on spot 1 collected morning, on spot 2 collected afternoon, and on spot 3 collected evening, sample urine collected from 44 healthy children age 10-13 years. UIC of 24-hour urine and one spot urine analyzed in the laboratory GAKY FK UNDIP using acid digestion method.Results: The average UIC from 24-hour urine collection was 179.77 ± 56.4 µg/l and UIC from on spot urine collection were on spot morning 145.30 ± 63.6 µg/l, on spot afternoon 159.95 ± 64.5 µg/l, and on spot evening 167.50 ± 66.1 µg/l. However, UIC correlation between UIC from on spot afternoon and UIC 24-hour (r = 0.456) with 66.67 % sensitivity and 75.61 % specificity.Conclusion: UIC urine samples from lunch to dinner more accurately reflects the UIC 24 hours to categorize the iodine status of the population. UIC from spot urine samples collected on the afternoon can be used as an alternative to evaluate the iodine status of school-age children.